The Influence of Teacher and Student Interaction on the Social Development of Elementary School Students - Tasik, Yunita; Hidayat, Irsyad; Halim, Arif (Educia Journal, 2024)
The research examines how classroom activity’s structure and teacher facilitation and empathy combine to affect the formation of collaborative abilities in students enrolled in elementary school. The qualifying study used two elementary schools to collect data from 10 teachers who worked with 30 students between grades 3 to 5. The research collected its data through interviews combined with discussions and classroom observations and document analysis. Group activities that operate smoothly lead students to develop their teamwork abilities as well as their communication skills and their skills for resolving conflicts. Research established that students require the direction and compassion from teachers along with an encouraging learning space to develop their group working capabilities. Students gained increased confidence when working with fellow classmates which coincided with a heightened level of respect and empathy between peers. Research fills an academic void because it defines the role of teacher-led structured activities in advancing social development particularly among elementary school students. These activities create long-standing advantages which students retain to enhance their future cooperative work both in academic studies and social settings. Educators should adopt structured group tasks due to their confirmed ability to develop crucial social abilities while enhancing classroom relationships.